2014
DOI: 10.1007/s12263-014-0428-0
|View full text |Cite
|
Sign up to set email alerts
|

β-Cryptoxanthin modulates the response to phytosterols in post-menopausal women carrying NPC1L1 L272L and ABCG8 A632 V polymorphisms: an exploratory study

Abstract: Phytosterol (PS) intake may be used for hypercholesterolaemia in some groups although the presence of non-responders is well known. Carotenoids and PS/ cholesterol may compete for the same transporters during absorption. As part of a randomized, double-blind, crossover, multiple-dose supplementation study with b-cryptoxanthin (b-Cx) and PS, single and combined, polymorphisms of ABCG8 (A632V) and NCPL1 (L272L) were determined in 19 post-menopausal women. Subjects carrying CC polymorphism for NCP1L1 (L272L) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It is now well-established that dietary plant sterols (PS) can inhibit intestinal cholesterol absorption through several mechanisms, such as competition for incorporation into mixed micelles, hydrolysis of esters by digestive enzymes, enterocyte uptake by NPC1L1, and incorporation into chylomicrons [ 34 , 37 ]. In a randomized crossover supplementation study involving 19 post-menopausal females, participants carrying the CC genotype at rs2072183 (a synonymous variant with leucine at 272, published as L272L) in NPC1L1 showed significantly different changes in serum TC and LDL-C concentrations (0.38 ± 0.29 and 0.33 ± 0.29 mmol/L, respectively) compared to carriers of the G allele (−0.29 ± 0.10, and −0.18 ± 0.12 mmol/L, respectively) after consuming for four weeks a beverage providing 1.5 g PS/d [ 16 ]. Of note, these differences were no longer significant when an outlier in the participants homozygous for the minor allele was excluded from the statistical analysis.…”
Section: Studies Investigating the Effect Of Snps Taken Individualmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well-established that dietary plant sterols (PS) can inhibit intestinal cholesterol absorption through several mechanisms, such as competition for incorporation into mixed micelles, hydrolysis of esters by digestive enzymes, enterocyte uptake by NPC1L1, and incorporation into chylomicrons [ 34 , 37 ]. In a randomized crossover supplementation study involving 19 post-menopausal females, participants carrying the CC genotype at rs2072183 (a synonymous variant with leucine at 272, published as L272L) in NPC1L1 showed significantly different changes in serum TC and LDL-C concentrations (0.38 ± 0.29 and 0.33 ± 0.29 mmol/L, respectively) compared to carriers of the G allele (−0.29 ± 0.10, and −0.18 ± 0.12 mmol/L, respectively) after consuming for four weeks a beverage providing 1.5 g PS/d [ 16 ]. Of note, these differences were no longer significant when an outlier in the participants homozygous for the minor allele was excluded from the statistical analysis.…”
Section: Studies Investigating the Effect Of Snps Taken Individualmentioning
confidence: 99%
“…These data replicate, to some extent, previous associations described among Spanish children [ 45 ], where male carriers of the ABCG5 rs6720173-G allele had higher plasma TC and LDL-C concentrations with a daily intake of 14.3–34.1 g saturated fatty acids (SFA) compared to CC homozygotes [ 45 ]. Another crossover multiple-dose supplementation study with beta-cryptoxanthin and PS in healthy postmenopausal females showed that carriers of the CC genotype of ABCG8 rs6544718 (published as A632V, a missense variant, as defined by the amino acid change) had lower serum TC concentrations (−0.34 ± 0.09 mmol/L) compared to carriers of the T allele (0.08 ± 0.20 mmol/L) after consuming a beverage providing 1.5 g/d of PS plus 750 µg beta-cryptoxanthin over 4 wk [ 16 ].…”
Section: Studies Investigating the Effect Of Snps Taken Individualmentioning
confidence: 99%
“…Some of the most important carotenoids in terms of biotechnological and biomedical uses explored so far are: Astaxanthin (3,3′-dihydroxy-β,β′-carotene-4,4′-dione) [ 36 , 39 , 40 ], β-Carotene (β,β-carotene) [ 38 , 41 , 42 , 43 , 44 ], Canthaxanthin (β,β-carotene-4,4′-dione) [ 45 , 46 , 47 , 48 ], β-Cryptoxanthin (hydroxy-β-carotene) [ 38 , 49 , 50 , 51 , 52 , 53 , 54 ], Fucoxanthin [ 38 , 55 ], Lycopene (ψ,ψ-carotene) [ 33 , 56 , 57 ], Lutein (β,ε-carotene-3,3′-diol) [ 42 , 58 , 59 , 60 , 61 ], Zeaxanthin (β,β-carotene-3,3′-diol) [ 38 , 62 , 63 ], and Violaxanthin (5,6:5′,6′-diepoxy-5,5′,6,6′-tetrahydro-β-carotene-3,3′-diol) [ 64 , 65 , 66 , 67 , 68 ].…”
Section: Carotenoids: Structure and Functionalitymentioning
confidence: 99%
“…As described above, rs3808607, rs2072183, and rs1761667 were associated with increased serum cholesterol levels [30,33,34]. In addition, the mean age of the women included in this study was 64.3 years, suggesting that most were menopausal or postmenopausal.…”
Section: Discussionmentioning
confidence: 53%
“…CYP7A1 and NPC1L1 are involved in cholesterol metabolism. Both the T-allele of rs3808607 and C-allele of rs2072183, associated with the HR phenotype, were found to be involved in the insensitivity of phytosterol-dependent decrease in serum TC levels [30,31]. In addition, the A-allele of rs1761667, associated with the HR phenotype, increased the ratio of people exhibiting high serum cholesterol levels [32].…”
Section: Discussionmentioning
confidence: 99%